2017
DOI: 10.1177/1556264617713098
|View full text |Cite
|
Sign up to set email alerts
|

The Meanings of Helping: An Analysis of Cystic Fibrosis Patients’ Reasons for Participating in Biomedical Research

Abstract: Research participants often report wanting to help as a reason for participation, but who they want to help and why is rarely explored. We examined meanings associated with helping among 21 adults with cystic fibrosis (CF)-a group with high participation in research. Meanings included helping to advance research, helping others with CF, helping as their job, helping themselves, helping because they are special, and helping to give back. While some meanings were primarily oriented toward helping others, some al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…On the one hand, some participant accounts venture into therapeutic misconception (i.e., the tendency to misperceive research as treatment). On the other hand, the structural interrelation between research and care for participants as well as their nuanced understandings of the situation echo findings of other studies that question the practicality of binary distinctions between research and care for research ethics including the ideal of a purely altruistic neutral and autonomous research participant ( 28 32 ). Overall, the findings of this study highlight the importance of incorporating the lived experience of CF into ethical research design and implementation.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…On the one hand, some participant accounts venture into therapeutic misconception (i.e., the tendency to misperceive research as treatment). On the other hand, the structural interrelation between research and care for participants as well as their nuanced understandings of the situation echo findings of other studies that question the practicality of binary distinctions between research and care for research ethics including the ideal of a purely altruistic neutral and autonomous research participant ( 28 32 ). Overall, the findings of this study highlight the importance of incorporating the lived experience of CF into ethical research design and implementation.…”
Section: Discussionsupporting
confidence: 58%
“…Life not merely as the prevention of death, but life as improved longevity and overall wellbeing. The various ways patients and caregivers articulated their research participation in this study were reminiscent of the findings of Christofides et al ( 28 ) on research participation as a complex helping behavior that simultaneously encompasses prosocial motivations and “a nuanced understanding of the interconnectedness of research and treatment” [p.180 ( 28 )]. Such an interconnected understanding was compounded by the fact that research often takes place in the same settings in which participants receive CF care, that both research participation and care are ongoing aspects of their lifelong medicalization and that progression of their medications and therapies is interwoven with research advancements ( 27 29 ).…”
Section: Discussionmentioning
confidence: 78%
“…In the later years of research on TM, it became apparent that although some participants do not understand that trials are not treatment, it is often the case that when enrollees say that they hope that the trial gives them a medical benefit, it is not that they are misinformed about the purpose of a trial (Kim et al, 2009). Rather, they are often desperate and are hoping for the remote possibility of receiving medical benefit (Christofides et al, 2017), or for any number of positive psychological functions that hope serves (Sulmasy et al, 2010). In light of these developments, scholars now make a distinction between true TM, which is apparently more rare, and “therapeutic optimism,” where “prospective participants and actual research subjects understand the likelihood of benefit but hope they will personally benefit from participation” (Sisk & Kodish, 2018, p. 14).…”
Section: Empirical Studies Of Self-interest and Altruism In Trial Enrmentioning
confidence: 99%
“…These types of considerations are not unique to this particular sample of participants. The importance of "wanting to help" was also observed in an adult sample of participants with CF (Christofides et al 2017). Other studies have also shown that trust plays an important role in decisions about research participation, specifically trust in the researcher, the institution, and the consent process (Dixon-Woods et al 2006;Woodgate and Edwards 2010).…”
Section: Beyond Isolated Subjects: Relational Understandings Of Persomentioning
confidence: 77%